Penyeliaan latihan mengajar secara elektronik(e-supervision): satu kajian kes di fakulti pendidikan, Universiti Teknologi Malaysia - Sulaiman, Esah; Aris, Baharuddin; Ali, Mohamad Bilal; Sharifuddin, Rio Sumarni; Tasir, Zaidatun; Zahiri, Megat Aman; Atan, Noor Azean; Abdullah, Zaleha; Sidek, Rosni Zamuddin Shah (Faculty of Education, 2008)
Teaching practicum is designed to give students supervised practical application of previously studied theory. It is a compulsory course for student teachers in Malaysia University of Technology (UTM). This course will provide an overview of teaching methods and the fundamentals of the teaching profession through lecture and practicum based on clinical supervision. Pre pedagogical techniques will be discussed or supervised and it will be finalized with post teaching. In order to sustain and improvise the existing supervision, a new strategy is required and the development of ICT technology in education should be able to facilitate. â€œE-Supervisionâ€? or known as electronic supervision provides essential communication between students and supervisor through email and web system formed. An E-Supervision system has been implemented and a study has been done to examine its effectiveness towards management during teaching practicum in schools. Data compilation demonstrates good responds from the student teachers who experienced it.